Asylum, Work, and Precarity Bordering the Asia-Pacific - Henry, Nicholas (Critical Studies of the Asia-Pacific,, 2018)
This book explores the regional coordination and impact of state responses to irregular migration in Southeast Asia and the Pacific. The main argument is that regional and international trends of securitisation and criminalisation of irregular migration, often associated with framing the issue in terms of migrant smuggling and human trafficking, have intensified carceral border regimes and produced greater precarity for migrants. Bilateral and multilateral processes of regional coordination at multiple levels of government are analysed with a focus on the impact on asylum seekers and migrant workers in major destination and transit countries including Malaysia, Thailand, Singapore, Indonesia, and Australia. The book will be of interest to a wide academic audience interested in the interdisciplinary field of Border Studies, as well as general readers concerned with the treatment of refugees and migrant workers who cross borders in search of safety, security, and a better life.